The Effect of The Number of Companies, The Number of Labor and Input Costs in The Tobacco Processing Industry on Increasing Output Value of Tobacco Processing Results in East Java Province - yustie, renta yustie (Jurnal Ilmu Ekonomi Terapan, 2018)
The concept of the development of a country and region can be linked to the process of industrialization. The industrialization process makes human resources act based on rational considerations. The industry developed in East Java Province is the tobacco processing industry. Tobacco is one of the trading commodities that has a very strategic role. Empowerment and development of tobacco involves millions of people and generates sources of foreign exchange, a potential source of tax in East Java Province. The output of the tobacco processing industry is the final product that is close to the user or consumer.This study uses independent variables, namely the number of companies, the amount of labor and input costs of the tobacco processing industry. The dependent variable in this study is the output value of the results of the tobacco processing industry. The time of the study was 2011-2015 and the research area in East Java Province. The method used in the study is the OLS method and with multiple linear regression models.